2008
DOI: 10.2135/cropsci2007.01.0018
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Traits Improvement and Associations in Hard Red Spring Wheat Cultivars Released in North Dakota from 1968 to 2006

Abstract: Periodic evaluation of cultivars allows researchers to evaluate genetic variation and progress made in various traits. Determining genetic gain or lack can lead researchers to develop new strategies for trait improvements. A two‐year study was initiated in 2004 to examine the changes in agronomic performance of hard red spring wheat (HRSW) (Triticum aestivum L.) cultivars released by North Dakota State University (NDSU) over the past 40 years. The experiment was conducted in North Dakota at three sites in 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
31
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 13 publications
7
31
2
4
Order By: Relevance
“…Some studies showed a significant decrease in days to heading (Guarda et al 2004;Lopes et al 2012). Our results are consistent with other publications (Underdahl et al 2008;Graybosch and Peterson 2010;Mladenov et al 2011;Mustaoea and Saulescu 2011) where increased grain yield was achieved without extending the crop-ping season (Fig. 1(I)).…”
Section: Cereal Research Communications 42 2014supporting
confidence: 93%
“…Some studies showed a significant decrease in days to heading (Guarda et al 2004;Lopes et al 2012). Our results are consistent with other publications (Underdahl et al 2008;Graybosch and Peterson 2010;Mladenov et al 2011;Mustaoea and Saulescu 2011) where increased grain yield was achieved without extending the crop-ping season (Fig. 1(I)).…”
Section: Cereal Research Communications 42 2014supporting
confidence: 93%
“…Generally, when results for all cultivars were compared, lodging was significantly higher (P < 0.05) at high N (32%) than at low N-level (18%). The estimated average decrease in lodging of 1.56% per year, was between values obtained by Underdahl et al (2008) Level of statistical significance: * P < 0.05; ** P < 0.01; and ns: not significant.…”
Section: Grain Yieldmentioning
confidence: 70%
“…Empirical studies of this type generally examine only a few cycles of selection (Mitchell et al, 1992;Courtois et al, 1993). Examples include wheat (Triticum aestivum L.) in North Dakota (Underdahl et al, 2008) and the Illinois long-term corn (Zea mays L.) selection experiment (Hagdorn et al, 2003;Dudley 2007). Another approach is to evaluate changes in traits among released cultivars over longer periods of time.…”
Section: Eff Ect Of Advanced Cycle Breeding On Genetic Gain and Phenomentioning
confidence: 99%